Anaerobic Oxalate Degradation: Widespread Natural Occurrence in Aquatic Sediments - Smith, Richard L. (1983)
Significant concentrations of oxalate (dissolved plus particulate) were present in sediments taken from a diversity of aquatic environments, ranging from 0.1 to 0.7 mmol/liter of sediment. These included pelagic and littoral sediments from two freshwater lakes (Searsville Lake, Calif., and Lake Tahoe, Calif.), a hypersaline, meromictic, alkaline lake (Big Soda Lake, Nev.), and a South San Francisco Bay mud flat and salt marsh. The oxalate concentration of several plant species which are potential detrital inputs to these aquatic sediments ranged from 0.1 to 5.0% (wt/wt). In experiments with litter bags, the oxalate content of Myriophyllum sp. samples buried in freshwater littoral sediments decreased to 7% of the original value in 175 days. This suggests that plant detritus is a potential source of the oxalate within these sediments. [(14)C]oxalic acid was anaerobically degraded to (14)CO(2) in all sediment types tested, with higher rates evident in littoral sediments than in the pelagic sediments of the lakes studied. The turnover time of the added [(14)C]oxalate was less than 1 day in Searsville Lake littoral sediments. The total sediment oxalate concentration did not vary significantly between littoral and pelagic sediments and therefore did not appear to be controlling the rate of oxalate degradation. However, depth profiles of [(14)C]oxalate mineralization and dissolved oxalate concentration were closely correlated in freshwater littoral sediments; both were greatest in the surface sediments (0 to 5 cm) and decreased with depth. The dissolved oxalate concentration (9.1 μmol/liter of sediment) was only 3% of the total extractable oxalate (277 μmol/liter of sediment) at the sediment surface. These results suggest that anaerobic oxalate degradation is a widespread phenomenon in aquatic sediments and may be limited by the dissolved oxalate concentration within these sediments.